Global Projects, Local Histories: Tradition, Digital Activism, and Resistance in the Indigenous Esports Movement in Brazil - Macedo, Tarcízio (AoIR Selected Papers of Internet Research, 2026)
Electronic sports (esports) have emerged as a crucial space for Indigenous players in Brazil, particularly through the game Free Fire (FF), which is accessible via mobile devices. The increasing adoption of smartphones has enabled the formation of Indigenous teams across different regions of the country, creating new spaces for resistance and digital visibility. This ethnographic study explores the knowledge practices and gaming approaches of players from four Indigenous groups in Brazil: Apunirã, Ava-Guarani, Guarani, and Xakriabá. Grounded in experiential ethnography and decolonial Oral History, the research examines how these players negotiate their identities and advocate for Indigenous rights within the esports ecosystem, which has traditionally been dominated by non-Indigenous actors. Indigenous players utilize esports as a tool for digital activism, challenging stereotypes and denouncing political threats such as the “temporal framework” thesis, which underpins Brazil’s Law 14.701/23. Through esports platforms and digital social networks, they amplify their struggle for territorial rights and environmental justice, demonstrating that Indigenous participation in technology does not contradict their cultural identities but rather reinforces their presence in digital spaces. In this way, esports move beyond being merely a site of entertainment and become a space for digital sovereignty and decolonial resistance. This study contributes to the understanding of digital games through an ethno-racial perspective, highlighting how Indigenous players reframe gaming spaces to challenge colonial structures and assert their political and cultural existence.